Innovation and digitalization as factors in the transformation of excursion practice - Lysyuk, Tatiana V.; Biletskyi, Yurii V.; Royko, Larysa L. (The University of Technology in Katowice Press, 2025)
The article provides a comprehensive analysis of innovative approaches to the digitization of excursion activities, including the use of virtual (VR) and augmented (AR) reality, mobile applications, AI-based audio guides, geolocation services, and interactive multimedia platforms. The study focuses on the transformation of traditional excursions into digital formats that ensure the accessibility of tourist services regardless of the user's geographical location, promote the personalization of experiences, and expand opportunities for interaction with cultural heritage. The results presented highlight the role of innovation as a catalyst for competitiveness in tourism and define the vectors for the further development of excursion activities in the context of digital transformation
Keywords: excursion; excursion practice; іnnovation; digitalization factors